Eksplorasi Etnomatematika pada Tiang Rumah Budaya Sumba Kabupaten Sumba Barat Daya dan Penerapannya dalam Pembelajaran Matematika - Lende, Rosalia; Ratus, Adeodatus; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Identify the mathematical aspects found in the pillars of the sumbanese cultural house in southwest sumba regency:and 2) apply these mathematical aspects to mathematics learning. This research was conducted in kalembu Ngabanga waitabula village, sounhwest sumba regency. This research is a descriptive qualitative study. Date were obtained from interviews with one of the informants, namely the guest host of the sumbanese cultural house. The interview data consisted of an analysis of the pillars of the sumbanese cultural house in southwest sumba regency, which were then examined for mathematical aspects based on several activities. The pillars of the sumbanese cultural house in southwest sumba regency, which werw then examined for mathematical aspects, such as cylinders, but on the pillars yhere are several carvings that have mathematical aspects, such as triangles and circles.